2020
DOI: 10.1002/open.202000287
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid‐Driven Formation of and Cation Exchange in Layered Sulfido Stannates – a CH2 Group Makes the Difference

Abstract: Two types of layered sulfido stannates or a molecular cluster compound are obtained upon ionothermal treatment of the simple sulfido stannate salt K4[SnS4] ·  4H2O that is based on binary tetrahedral [SnS4]4− anions. The formation of the respective products, novel compounds (C4C1C1Im)2[Sn3S7] (1 a), (C4C1C2Im)2[Sn3S7] (1 b), and (C4C1C2Im)2[Sn4S9] (2) with layered anionic substructures, or the recently reported compound (C4C1C1Im)4+x[Sn10O4S16(SMe)4][An]x (A) comprising a molecular cluster anion, is controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In FJSM-SnS-3, the interlaminar distance containing the mixed [CH 3 NH 3 ] + and [Bmmim] + is estimated to be 11.383 Å, which is bigger than that of FJSM-SnS-2. Although thiostannates containing a 2D anionic [Sn 3 S 7 ] n 2 n– network with a variety of cations have been reported (see Table S2), , it is first found that interlayer spaces of [Sn 3 S 7 ] n 2 n– accommodate the mixed cations of large-sized ionic liquid cations and small-sized protonated organic amines in FJSM-SnS-2 and FJSM-SnS-3. The arrangements of two types of cations between different layers are extremely rare for layered sulfides, showing the unique charm of the mixed template method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In FJSM-SnS-3, the interlaminar distance containing the mixed [CH 3 NH 3 ] + and [Bmmim] + is estimated to be 11.383 Å, which is bigger than that of FJSM-SnS-2. Although thiostannates containing a 2D anionic [Sn 3 S 7 ] n 2 n– network with a variety of cations have been reported (see Table S2), , it is first found that interlayer spaces of [Sn 3 S 7 ] n 2 n– accommodate the mixed cations of large-sized ionic liquid cations and small-sized protonated organic amines in FJSM-SnS-2 and FJSM-SnS-3. The arrangements of two types of cations between different layers are extremely rare for layered sulfides, showing the unique charm of the mixed template method.…”
Section: Resultsmentioning
confidence: 99%
“…The development of metal sulfide ion exchangers greatly depends on the improvement of synthesis methods. The ionothermal method has recently caught attention due to the specific ionic environment of ionic liquids (ILs) with unique solvent properties aiding the formation of novel compounds that are inaccessible in molecular solvents. The cation of ILs (typically imidazolium cations) can act as a charge balance agent and structure directing agent to induce the formation of 2D layered or 3D microporous frameworks. However, 2D and 3D chalcogenides synthesized by the ionothermal method mainly focus on metal selenides up to now. The open frameworks of metal sulfides prepared in ILs are still rare …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation